Protective effects of selenium, vitamin C and vitamin E against oxidative stress of cigarette smoke in rats - Dilsiz, N; Olcucu, A; Cay, M; Naziroglu, M; Çobanoglu, D (Wiley, 1999)
Cataractous lenses have been found to have an alter ed distribution of the intracellular ionice environment: the concentrations of potassium and magnesium being decreased and the concentrations of sodium and calcium increased. These changes arise as a result of changes to lens membrane characteristics causing an increase in lens membrane permeability. In this study flame atomic absorption spectroscopy (AAS) was used for calcium, magnesium, iron and zinc determination, and flame atomic emission spectroscopy (AES) was used for sodium and potassium contents in normal and cigarette smoke-exposed rat lenses. The methods are sensitive enough to detect quantitatively all six cations in a single rat lenses, In this work, six elements, including Ca2+, K+, Na+, Zn2+, Fe2+ and Mg2+ in experimental rat eye lenses and normal transparent lenses were determined. It was found that the concentrations of Ca2+, Na+, Zn2+, and Fe2+ were increased dramatically while K+ and Mg2+ decreased in smoke-exposed rat lenses when compared to the control rat lenses. There were no significant changes between 'smoked' rats supplied with vitamin C and control groups. A positive correlation was found also in the other two groups of 'cigarette smoked' animals supplemented with selenium plus vitamin E and selenium when compared with 'cigarette smoked' without any supplements. These data provide support for the hypothesis that cigarette smoking increases the risk of cataract formation. We investigated whether vitamin C is the most important antioxidant in the body. The roles of diet with optimum amounts of antioxidant vitamins C and vitamin E and the antioxidant mineral selenium are discussed. Copyright (C) 1999 John Wiley & Sons. Ltd.
Keywords: cataract; selenium; vitamin E; vitamin C; minerals; atomic absorption spectrophotometer; flame atomic emission spectrophotometer